Isolation of three metabolites from the plant Cajanus cajan ( L.) Huth and evaluation of antibacterial and cytotoxic potentials of extract of Cajanus cajan (L.) Huth available in Bangladesh (Bangladesh Journal of Scientific and Industrial Research, 2025)
The chemical and biological aspects of the Fabaceae  plant Cajanus cajan (L.) Huth are the focus of this investigation. Some research has been done on these species, but Bangladeshi species has not been substantially explored. The leaf of Cajanus cajan (L.) Huth was cold extracted with methanol and subjected to column chromatography for fractionation over silica gel, successively with n-hexane, mixtures of n-hexane/CH2Cl2, CH2Cl2 itself, mixtures of CH2Cl2/CH3OH and CH3OH respectively. The crude methanolic extract and column fractions were phytochemically analysed to identify active components and biologically tested for pharmacological properties. The two stilbene metabolites: cajaninstilbene acid and longistylin A and one sterol, stigmasterol were isolated and identified by a combination of repeated column chromatography and solvent treatment. Some column fractions of methanol leaf extract exhibited significant antibacterial activity at a concentration of 200 µg/disc against a number of both Gram-positive and Gram-negative bacteria by disc diffusion method. Moreover, most of the column fractions demonstrated  significant cytotoxicity in brine shrimp lethality bioassay.Bangladesh J. Sci. Ind. Res. 60(1), 01-08, 2025